Fuzzy Mapping on Psychological Disorders in Construction Management - Wang, Chen; Mohd-Rahim, Faizul Azli; Chan, Yit Yee; Abdul-Rahman, Hamzah (American Society of Civil Engineers, 2017)
Work-related stress in construction management can trigger impairment to employees' psychological health, and thus affect project performance, but psychological disorders' deleterious consequences on project performance have not received sufficient attention in the literature. This study aims to identify different types of psychological disorders in construction projects and to develop a fuzzy mapping to determine the impact of psychological disorders in the context of time, cost, and quality in construction management. Through a questionnaire survey assisted by pair-wise comparison among experienced construction personnel, the six most common psychological disorders, including depression, generalized anxiety disorders (GAD), obsessive-compulsive disorders (OCD), substance use disorders (SUD), acrophobia, and claustrophobia, were analyzed using principal component analysis (PCA), partial least-square (PLS) tests, and fuzzy analytic hierarchy process (fuzzy-AHP), and followed by visualization. Although various stressors such as work overload, role ambiguity and conflict, unpaid overtime, restrictive career progression, and the diverse range of personalities are common in construction management, different roles and positions are subjected to different levels of stress, which from high to low are project manager, civil engineer, architect, contractor, quantity surveyor, and mechanical and electrical (M&E) engineer. This research developed fuzzy mapping of psychological disorders in the context of project performance, which is useful for project management teams to reveal and tackle mental health problems in early stages.